Effects of a One-week Vacation with Various Activity Programs on Metabolism and Adipokines - Neumayr, Günther; Engler, Clemens; Lunger, Lukas; Lechleitner, Peter (International Journal of Sports Medicine, 2020)
This study was conducted as part of a larger study of East Tyrolean health tourism, and investigates the effects of an active seven-day vacation on metabolic parameters and adipokines. Fifty-two healthy vacationers participated in two types of vacation activities (golf vs. Nordic walking or e-biking [nw&eb]). In the former group, 30 subjects played golf for a mean duration of 33.5 h per week; in the NW&EB group, 22 persons performed Nordic walking or e-biking for a mean duration of 14.2 h per week. Metabolic parameters and adipokines, such as leptin, adiponectin, GF-21, irisin, omentin-1, betatrophin, and resistin, were measured one day before and one day after the stay. After one week, only the NW&EB group experienced a significant decrease of 1.0 kg in body weight. Significant changes in HDL-C, FGF-21, irisin, and omentin-1 were seen in the golf group; and in triglycerides, HbA1c, leptin and adiponectin in the NW&EB group. No significant changes in betatrophin or resistin were registered in either group. A seven-day vacation with an activity program for several hours per week causes favorable changes in metabolic parameters and adipokines known to be involved in the pathophysiology of the metabolic syndrome. The changes differed in their magnitude and significance, depending on the type of activity.
Keywords: golf; walking; bicycling; health resorts; adipokines